Penerapan Capaian Pratik Dalam Meningkatakan Kompetensi Siswa Pada Mata Pelajaran Instalasi Motor Listrik - Aulia, Ersa Diva; Muskhir, Mukhlidi (Jurnal Pendidikan Teknik Elektro, 2025)
The problem of this research is the lack of student competence in the field of practice, several problems were found including: students are not accustomed to using practical tools, students cannot interact with work objects, students find it difficult to understand work steps, lack of understanding of work safety, students ignore the use of PPE, lack of cleanliness, and so on. So the researcher will research “The application of practical achievements in improving student competence in the subject of Electric Motor Installation in class XI TKL SMK N 1 Bukittinggi”. This study aims to determine the impact of applying 8 indicators of practical ability on students' P2 knowledge level. This research is a type of quantitative descriptive research using experimental methods with Pre- pre-experimental designs, one-group pretest-posttest, and assessment rubrics. The number of respondents was 32. The results of this study were tested using SPSS 26 with descriptive statistical analysis, t-test, F test, multiple regression analysis, analysis of variance, gain score test, and effect size. Based on the results of the study, the N Gain Score value was 0.3365 with a medium category, and the effect size with Cohen's d was 1.277 with a large category. So the application of these 8 indicators of practical ability is proven to improve students' P2 skills. This research could have been used as a further reference to develop more effective learning strategies and curriculum enhancements to meet students' needs.